CHARACTERIZATION OF ACTIVATED CARBON AND APPLICATION OF COPPER REMOVAL FROM DRINKING WATER - Kalpakli, Yasemen Kutmen; Koyuncu, Ikbal (WALTER DE GRUYTER GMBH, 2009)
In this study, removal of copper ions from aqueous solution by adsorption was investigated. The methods were applied to removal of copper in artificial water and drinking water samples using activated carbon. For this purpose, metal removal from water depends on the pH. The initial concentration of metal, amount of activated carbon, and effect of sorption time were investigated. The process parameters were investigated with batch studies In this study, commercial activated carbon, Chemviron C-1300, has been used. Granular activated carbon were characterized using nitrogen porosimetry, pH titration, Boehm's titration, mercury porosimetry, FTIR and scanning electron microscope measurements. The copper ions were determined by an atomic absorption spectrometry. Optimum conditions were found as concentration of 10 mg l(-1), pH: 5, contact time:25 min, and activated carbon amount:750 mg. Optimum condition were applied to drinking water for removal of Cu(II). Furthermore, adsorption isotherm data were fined to both Langmuir and Freundlich models for finding the optimum conditions.
Keywords: Drinking water; Heavy metal; Atomic absorption spectrometry; Activated Carbon; Physico-chemical characterization; Adsorption isotherm; ADSORPTION; ACIDITY; ZINC; Chemistry